2023
DOI: 10.3389/fpsyg.2023.1146732
|View full text |Cite
|
Sign up to set email alerts
|

Agentic and communal narcissism in predicting different types of lies in romantic relationships

Abstract: Several studies have investigated a potential positive association between agentic narcissism and general dishonesty, revealing both supportive and contradicting evidence. Few have focused on dishonesty within romantic relationships, a phenomenon that occurs in almost all partnerships. With the present research, we first aimed to extend existing literature on narcissism by including its two complementary facets (i.e., agentic and communal narcissism). Second, we aimed to improve the understanding of narcissist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The relationship between the CEMA-A and EPQ-R factors confirms convergent validity and evidences the role of personality in the motives for lying ( Buller and Burgoon, 1996 ; Olson and Weber, 2004 ; McLeod and Genereux, 2008 ; Harhoff et al, 2023 ). One study found that coldness when lying (e.g., “I do not usually have remorse when I lie”) was positively related to Psychoticism, whereas emotional self-regulation when lying (e.g., “I feel guilty when I’m caught in a lie”) was negatively related.…”
Section: Discussionsupporting
confidence: 64%
“…The relationship between the CEMA-A and EPQ-R factors confirms convergent validity and evidences the role of personality in the motives for lying ( Buller and Burgoon, 1996 ; Olson and Weber, 2004 ; McLeod and Genereux, 2008 ; Harhoff et al, 2023 ). One study found that coldness when lying (e.g., “I do not usually have remorse when I lie”) was positively related to Psychoticism, whereas emotional self-regulation when lying (e.g., “I feel guilty when I’m caught in a lie”) was negatively related.…”
Section: Discussionsupporting
confidence: 64%